You Really Just Did That!? Pet Peeves of College Advisors and Advisees - Lamers, Rebecca J.; Morgan, Kristen; Remington, Katie L.; Shipman, Ashley E.; Wallin, Robyn S. (My University, 2013)
This study analyzed annoying, bothersome, or irritating behaviors of advisees and advisors at the University of Wisconsin-Eau Claire by deploying the Critical Incidence Technique (Flanagan, 1954).
Color poster with text and graphs.
Keywords: Pet peeves; College advisors; College students; Posters